Improved drilling rigs for underground various-purpose pipelines in difficult mining and geological conditions - D. Yu. Serikov; N. D. Tskhadaya; D. A. Boreyko (Известия высших учебных заведений: Геология и разведка)
Background. When constructing underground crossings of oil and gas pipelines using directional drilling, the task of enhancing the drilling efficiency becomes urgent. In particular, this concerns the conditions of increased hydraulic resistance and differential pressure. To solve this problem, we propose a new calibrator-ejector design.Aim. To improve the existing drilling technology by applying a new calibrator-ejector design. The proposed device is equipped with ejection systems for cleaning the borehole, thus increasing the efficiency of directional drilling.Materials and methods. The problem of increasing the efficiency and environmental friendliness of the process of pilot borehole expansion during the construction of underground crossings of oil and gas pipelines was solved by using reverse circulation and proposing a new design of the calibrator-ejector device.Results. The possibility of using the same tool at different stages of drilling is shown. This reduces the financial and time expenditures for the construction of crossings. The implementation of the proposed technologies facilitates management of the drilling process and reduces its negative impact on the environment, thus contributing to the development of directional drilling technologies.